2017
DOI: 10.1016/j.fusengdes.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the ASDEX Upgrade glow discharge

Abstract: The ASDEX Upgrade (AUG) system for glow discharge (GD) has been revised comprehensively. This was necessary due to technical as well as operational requirements. The available space with in the low field side of the vacuum vessel is strongly limited because it's the preferred place for diagnostics. The new development based on the design of the W7-X anode now has a smaller footprint, is long term reliable and easier maintainable. Additionally each of the anodes is equipped with a separate starting device. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Comparing different discharge duty cycles for GDC procedures with 5 minutes duration, it is found that 10-second-long discharges followed by 50 s for pumping are optimal. Retention of helium is reduced by 83.3% while removing still 68.7% of the hydrogen compared to continuous GDC operation [20]. The applicability of GDC for T-recovery in ITER is assessed by considering 5 operation days with a modest number of 10 pulses per day of 400 s each operated in JET.…”
Section: Maximising Removal (mentioning
confidence: 99%
“…Comparing different discharge duty cycles for GDC procedures with 5 minutes duration, it is found that 10-second-long discharges followed by 50 s for pumping are optimal. Retention of helium is reduced by 83.3% while removing still 68.7% of the hydrogen compared to continuous GDC operation [20]. The applicability of GDC for T-recovery in ITER is assessed by considering 5 operation days with a modest number of 10 pulses per day of 400 s each operated in JET.…”
Section: Maximising Removal (mentioning
confidence: 99%
“…On September 25, 2018, a Boronization [4], including an 8 h He glow discharge [6], was applied to optimize the wall conditions. Operation was started the next day.…”
Section: Restartmentioning
confidence: 99%
“…A significant disadvantage is the sputtering of materials in contact with the plasma, which leads to the deposition of metal films on the equipment located in it [8,9]. Despite this drawback, the technology of cleaning the wall of the vacuum chamber with a glow discharge plasma is the most common and is used in large installations, for example, in TEXTOR [8], Wendelstein 7-X [9][10][11], ASDEX-U [12], JET [13], LHD [14], EAST [15], SST-1 [16]. In the future, it is planned to use the GDC system at ITER [17].…”
Section: Introductionmentioning
confidence: 99%
“…Common to all systems is the use of a vacuum chamber wall as a cathode, and specially designed electrodes as anodes, which are placed into the vacuum volume. The number of electrodes (anodes) is usually from 2 (SST-1 [16], LHD [14]) to 4 (ASDEX-U [12], JET [13], EAST [15]). The electrodes (anodes) 10, are installed on Wendelstein 7-X [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation